Social Education Degree Student Facing Interdisciplinary Work: Challenges and opportunities for the development of good teaching - Bilbao Urquidi, Saioa; Eiguren Munitis, Amaia; Artetxe Sanchez, Karmele (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The Social Education Degree of the UPV/EHU, based on a modular structure, through the linking of the different subjects, encourages students to acquire and develop the required skills through reflection processes based on real cases. For this article, the path taken by the teaching team and the students in the last eleven years has been analyzed in the module called "Educational professions". For this, a documentary analysis of the systematized material has been carried out over these years and two teachers who were part of the first teaching team have been interviewed.